Incidencia en la recaudación de impuestos municipales en el presupuesto del Gobierno Autónomo Descentralizado del Cantón Puyango, Provincia de Loja periodo 2021-2022 - Ramón Calderón, Karen Estéfani (2023)
It is essential to acquire knowledge about the economic activities that sustain our country. Generally, there are two main sources of revenue generation: national taxes and municipal taxes, with the Internal Revenue Service being responsible for the administration of national taxes, while sectoral taxes are in charge of municipalities. Therefore, it is crucial to understand municipal tax collection, as it constitutes the main source of revenue for these institutions. The purpose of this research is to analyze the incidence in the collection of municipal taxes in the budget of the Decentralized Autonomous Government of the Puyango Canton, Province of Loja period 2021-2022, considering the approach of this study which was quantitative and qualitative, combining elements of analysis respectively. To achieve this purpose, interviews were conducted with the heads of the financial, income and treasury departments, since they are the ones who have extensive financial knowledge and can provide relevant information, which after carrying out the interviews and analyzing the information, some important conclusions were highlighted, among them, it was identified that there is a collection of 8.39% of what is estimated to be collected, In the same way, the lack of continuous disclosure, the need for adequate notification to delinquent citizens and the absence of an updated collection system are the factors that intervene in the lack of a good collection of taxes, facts that generate the proposal of strategies in order to mitigate this lack of collection. In conclusion, knowing the collection of municipal taxes and optimizing their management is crucial to ensure a constant flow of income for the municipal GAD of the Puyango canton; By implementing the proposed strategies, it is expected to improve the situation and achieve a more effective fulfillment of the objectives set by the municipality.